The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12931-017-0664-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum bilirubin and the risk of chronic obstructive pulmonary disease exacerbations

Abstract: BackgroundBilirubin is a potent anti-oxidant and higher serum concentrations of bilirubin have been associated with better lung function, slower lung function decline, and lower incidence of chronic obstructive pulmonary disease (COPD). We sought to determine whether elevated bilirubin blood concentrations are associated with lower risk for acute exacerbations of COPD (AECOPD).MethodsWe performed a secondary analyses of data in the Simvastatin for Prevention of Exacerbations in Moderate-to-Severe COPD (STATCOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…It suggests that bilirubin may has a protective effect on lung tissue by impressing the in ammation and oxidative stress response in lungs [31], and was associated with a lower risk of respiratory disease and all-cause mortality [32]. Kirstin E Brown et al [13]also showed, as in our study, that elevated serum bilirubin level are associated with a lower risk of AECOPD, hence it can be used as a biomarker of AECOPD risk.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It suggests that bilirubin may has a protective effect on lung tissue by impressing the in ammation and oxidative stress response in lungs [31], and was associated with a lower risk of respiratory disease and all-cause mortality [32]. Kirstin E Brown et al [13]also showed, as in our study, that elevated serum bilirubin level are associated with a lower risk of AECOPD, hence it can be used as a biomarker of AECOPD risk.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, researchers have found that neutrophil-to-lymphocyte ratio(NLR) can not only predict COPD progression and outcomes, but also an independent predictor of COPD mortality [9][10][11][12]. Bilirubin is also con rmed to be a protective index that associated with a lower rate of COPD progression and risk of exacerbation [13]. But up till now, few studies have explored the predictive value of NLR and bilirubin levels in the readmission of AECOPD.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of serum bilirubin on respiratory outcomes have been reported in several studies [ 5 , 6 , 12 ]. In a previous study by Temme et al, high serum bilirubin was associated with lower cancer mortality, including that of lung cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 In addition to its function as an oxidant scavenger, bilirubin protects lipids against oxidant stress and reduces intracellular reactive oxygen species (ROS) production by inhibiting membrane-bound nicotinamide adenine dinucleotide phosphate oxidase. 18 Numerous studies have confirmed the protective effects of bilirubin against oxidant stress-associated pulmonary diseases such as COPD. Moreover, serum bilirubin concentration has been implicated as the biomarker of severity and progression of COPD and an independent prognostic factor in non-small-cell lung cancer (NSCLC) following successful resection.…”
Section: Discussionmentioning
confidence: 98%
“…Based on previous studies, it has been proposed that baseline percent predicted of DLCO-SB is superior to baseline percent predicted FVC as a prognostic indicator in IPF. 23 Pulmonary function progression according to serum bilirubin levels in the healthy general population 13 and patients with COPD 18 have been investigated in human studies, but not in patients with IPF. In our study, serum TBIL and IBIL levels were found to correlate positively with percent predicted of DLCO-SB in IPF patients, while no association was observed between TBIL and pulmonary function, percent predicted of FVC, or percent predicted of FEV1.…”
Section: Discussionmentioning
confidence: 99%